Cognitive Linguistics: A Survey Of Linguistic Subfields - Dabrowska, Ewa and Divjak, Dagmar (De Gruyter, 2019)
The Chapters in this volume provide comprehensive surveys of the major subfields of Cognitive Linguistics. Apart from Phonology, construction grammar and lexical semantics, the areas of language use, language acquisition, variation and change and literary discourse are comprehensive presented.